Rice Availability Analysis in Kutai Kartanegara Regency 2023-2032 - Laode Muh Asdiq Hamsin Ramadan (P2M Politeknik Pertanian Negeri Samarinda, 2023)
East Kalimantan Province is one of the provinces with rice self-sufficiency agenda. Kutai Kartanegara is a regency in East Kalimantan Province with an area of ​​18659 ha of rice fields and is the largest rice supplier in the East Kalimantan region. So far there has been no research that examines the level of rice availability partially in the districts of East Kalimantan Province. This study aimed to predict population growth and the level of rice food security in Kutai Kartanegara Regency in 2023-2032. Develop various possible policy scenarios to achieve rice food security in Kutai Kartanegara Regency in 2023-2032. This research was conducted in the scope of Kutai Kartanegara Regency. The treatment of the research location was carried out purposively (purposive method) from April to May 2023. This research focused on one food commodity, namely rice. The results showed that Kutai Kartanegara Regency is predicted to experience a rice deficit in 2023-2032 with an average deficit of 32836.47 tons. Implementation of the existing rice field intensification policy can reduce the rice deficit that will occur until 2032 by 55%. The implementation of the new paddy field policy can reduce the rice deficit that will occur by up to 92%. The combination of the two land intensification policies and the creation of new rice fields can make Kutai Kartanegara Regency experience a surplus of rice until 2032 with an average surplus of 15613.86 tons.